2022
DOI: 10.1002/smll.202201473
|View full text |Cite
|
Sign up to set email alerts
|

NiSe and CoSe Topological Nodal‐Line Semimetals: A Sustainable Platform for Efficient Thermoplasmonics and Solar‐Driven Photothermal Membrane Distillation

Abstract: The control of heat at the nanoscale via the excitation of localized surface plasmons in nanoparticles (NPs) irradiated with light holds great potential in several fields (cancer therapy, catalysis, desalination). To date, most thermoplasmonic applications are based on Ag and Au NPs, whose cost of raw materials inevitably limits the scalability for industrial applications requiring large amounts of photothermal NPs, as in the case of desalination plants. On the other hand, alternative nanomaterials proposed so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 96 publications
(67 reference statements)
2
16
0
Order By: Relevance
“…Of particular interest for future studies will be NiTe 2 -based refractive index sensors, 2 perfect absorbers 36 for bio/chemical sensing, photodetection, solar energy harvesting, and even photothermal membrane distillation. 41 ■ ASSOCIATED CONTENT * sı Supporting Information…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of particular interest for future studies will be NiTe 2 -based refractive index sensors, 2 perfect absorbers 36 for bio/chemical sensing, photodetection, solar energy harvesting, and even photothermal membrane distillation. 41 ■ ASSOCIATED CONTENT * sı Supporting Information…”
Section: Discussionmentioning
confidence: 99%
“…These results provide the groundwork for an efficient harnessing of topological semimetals in nanophotonic applications. Of particular interest for future studies will be NiTe 2 -based refractive index sensors, perfect absorbers for bio/chemical sensing, photodetection, solar energy harvesting, and even photothermal membrane distillation …”
Section: Discussionmentioning
confidence: 99%
“…However, the implantation of NPs into the polymeric membrane not only increases its temperature and vapor flux but also increases its pore size and contact angle (>110°). As a result, the membrane exhibited much higher resistance to wetting [ 16 , 40 ]. In this regard, the wetting effect will be neglected and only the effects of implanted NPs and porosity on the membrane efficiency will be discussed.…”
Section: Resultsmentioning
confidence: 99%
“…Transition metal chalcogenide (TMCs) NPs have been proposed for use in photothermal therapy (PTT) treatments for cancer [ 37 , 38 ] and antibacterial membranes [ 39 ]. More recently, S. Abramovich et al [ 40 ] have shown that embedding NiSe and CoSe nanofillers into the polymeric membrane increases the transmembrane flux by 330% and 690%, respectively. These materials have strong photo absorption characteristics in a wide range of wavelengths and have shown to be less toxic than graphene, suggesting they might have a wide range of water treatment and biomedical applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation